Integrating Athlete Empowerment and Environmental Conservation through CSR Partnership: A Social Ecology Perspective on the Collaboration between Federasi Panjat Tebing Indonesia (FPTI) Kabupaten Lahat and PT Bukit Pembangkit Innovative - Ikhwana, Faza; Sahara, Tommy; Novianto, Imam Satrio; Sanjaya, Ikhsan; Pramadani, Oki (Prospect Publishing, 2025)
This study examines the integration of athlete empowerment and environmental conservation through the Corporate Social Responsibility (CSR) partnership of PT Bukit Pembangkit Innovative (BPI) in Lahat Regency, South Sumatra, using social ecology perspective by Murray Bookchin (1991). The research is grounded in the socio-ecological challenges posed by land-use change and forest degradation, alongside the potential of youth as agents of change. A descriptive qualitative approach was employed, involving in-depth interviews, participatory observation, and document analysis of two flagship programs: Pembinaan Federasi Panjat Tebing (FPTI) Kabupaten Lahat (Banjarsari Cipta Prestasi) and Bina Alam Hijau Asri Indah (BAHARI) Banjarsari (environmental conservation). Findings reveal that athlete training not only enhances physical capacity and sports achievements but also fosters ecological awareness through direct involvement in reforestation and greening activities across three villages, resulting in the planting of 400 trees with both ecological and economic value. Cross-sector collaboration—engaging the company, sports federation, village governments, local communities, and the Garis Milang organization—has created an inclusive and participatory socio-ecological network. In conclusion, PT BPI’s CSR partnership serves as an integrative medium that simultaneously advances human capacity building and environmental preservation. This model demonstrates the potential for replication in other regions, as it successfully combines sports excellence, community empowerment, and ecological sustainability within a unified strategic framework.